The Morbid Subject: A New Morphology for Analysis of the Phenomenon of Metamorphosis in Literature - Leopardi, Elisabetta (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of German, 2021)
"The Morbid Subject: A New Morphology for Analysis of the Phenomenon of Metamorphosis in Literature" is the author s attempt to formulate a cohesive and structured morphology for the phenomenon of metamorphosis as it appears in fiction. The study begins by establishing what is considered a proper (or genuine ) metamorphosis and the basic characteristics any transformation of this kind must exhibit to be deemed as such. Although academic work on this subject has been published at an almost epidemic frequency and scholarly interest has been described as bordering on morbidity, the nature of this phenomenon is still a matter of debate, plagued by unresolved disputes, misinterpretations, and arbitrary positions. The Introduction to this thesis aims to settle those issues before moving onto the formulation of a morphology. The morphology developed in this thesis is based on the initial postulation that any entity subjected to metamorphosis possesses three dimensions: a substance, a physical form, and a sensorial dimension. The choice of terminology and a concise overview of the three dimensions will be related in Chapter Two. Because each dimension can be metamorphically transformed, one of the aims of this study is to challenge the belief that metamorphosis exclusively entails a mutation in an entity s body. On the contrary, substantial and sensorial metamorphoses exist and are relevant forms of metamorphosis participating in the phenomenon. In Chapter Three, each dimension and its variables will be introduced and analysed individually. Variables are the features contained in a dimension; in other words, the attributes directly impacted by the transformation. The quantity and quality of these variables strictly depend on the dimension they belong to, and the ontological status of the entity involved (i.e., whether it is an object/inanimate matter or a sentient being). Each dimension may be affected by metamorphosis either totally or partially. When the metamorphosis alters the dimension totally, the whole dimension is transformed, meaning that all its variables are changed into something else. Conversely, when the metamorphosis is partial, only one or a number (but never all) of the dimension s variables are affected. After establishing the nature of the three dimensions and how their variables may be transformed, the last morphological step aims to formulate and enumerate the total number of theoretically possible forms of metamorphosis derived from a simple arithmetical calculus. By combining and re-combining the three dimensions and the extent to which each dimension may transform (or not transform) in the equation, it is possible to obtain a total of twenty-seven combinations, each corresponding to one expression/form of metamorphosis. Chapter Four will also focus on applying the morphology to fictional works by classifying individual episodes of metamorphosis into one of the twenty-seven modalities (combinations) of metamorphosis. Operating with a limited quantity of novels, novellas, short stories, and tales, for a total of one hundred and fifty-one metamorphoses examined, the success of the morphology will be measured on the number of combinations that appropriately fit those examples. The higher the number of combinations tracked in the literature selected for this dissertation, the higher the degree of the theory s legitimacy. The criteria selection for the texts used in the application stage was based on the popularity of these works in previous studies published on metamorphosis, provided that the metamorphosis discussed is a proper metamorphosis.
APPROVED
Keywords: Metamorphosis; Morphology; Comparative Literature